(untitled) - Frey, David (San Francisco, 2005)
Updated for the latest releases of AutoCAD and AutoCAD LT, this best-selling introductory book gives you a solid grounding in the essentials. You'll get instant gratification by following the step-by-step instructions and hands-on projects that cover each phase of designing a summer cabin. You can progress sequentially through the book or begin at any chapter by downloading the drawing files from the Sybex web site. Experienced author David Frey helps you acquire and practice your new skills, preparing you to delve into the more advanced topics and projects covered in George Omura's Mastering AutoCAD.
Keywords: AutoCAD,Computer graphics